Classical Unification of Gravitational and Electromagnetic Forces - Wang, Ling Jun (Edelweiss Applied Science and Technology, 2020)
We have presented a theory of unification of gravitational force and the electromagnetic force by generalizing Newton‟s law of gravitation to include a dynamic term similar to the Lorentz force of electromagnetic interaction. The inclusion of this dynamic term alone in the gravitational force is enough to develop the entire dynamic theory of gravitation parallel to that of electrodynamics. The theory naturally solves the mystery of action-at-distance. It has been shown that the inverse square law of the static and the dynamic forces is the result of the conservation of mass (Gauss‟s Law) and the total momentum (Wang‟s Law). The Wang‟s Law is a new discovery. The new theory also predicts that the gravitational wave is propagated at the speed of light.